Negative Childbirth Experience and Post-traumatic Stress Disorder - A Study Among Postpartum Women in South India - Shiva, Lakshmi; Desai, Geetha; Satyanarayana, Veena A.; Venkataram, Padmalatha; Chandra, Prabha S. (Frontiers in Psychiatry, 2021)
ABSTRACT Purpose: Negative childbirth experience has been associated with post-traumatic stress disorder (PTSD) and depression in the postpartum period with a significant impact on the mother as well as the infant. Methods: The current study aimed at studying the association of negative child birth experience with PTSD and depressive symptoms among primiparous mothers within 6 weeks of child birth. The Childbirth Experience Questionnaire (CEQ), PTSD checklist (PCL) and Edinburgh Postnatal Depression scale (EPDS) were used to assess negative childbirth experience, symptoms of PTSD and depression respectively. Results: Of the 95 women in the study, fifty women (52.6%) had a score below the median of CEQ score (score of 72) indicating a negative childbirth experience. Lower Scores on CEQ indicating negative childbirth experience correlated with PTSD scores on the PCL (r=-0.560, p=0.001) and depression scores on the EPDS (r= -0.536, p=0.001). Of the sample of 95 women, 7.36% (N=7) met the criteria for probable PTSD and 3.16% (N=3) met criteria for partial PTSD. Twelve women (12.6%) had EPDS scores above 13 indicating probable clinical depression. Median CEQ scores were lower among the women who had PTSD or partial PTSD (N=10) and among the women who had probable depression (N=12) than those who did not. Childbirth experience emerged as the only predictor of PTSD on logistic regression (p=0.03) (95% CI 1.17 – 79.61). Conclusions: Negative childbirth experiences are common and appear to be associated with depressive and PTSD symptoms. These findings emphasize the need to provide good intrapartum care including respectful maternity care for a positive childbirth experience.